(3GdQSGdI GdeTQbI HGdaUhd GdehfbIs
(3ChdgG (B:s
(3gPg QSGdI GYJeOJ ajgG GNJjGQc , hJhNjJ GHKGQc ajeG CQOJ Hg GdJ Ljd ef cJH GdJQSjd , hGbJUQJ Ydi YTQI aUhd s
(3BNQgG (B:s
(3eHJhQ BNQ GdehLhO efgG HYfhGf (B((3abQ ddfHjPjjf(B) (3eGNJeJ GdOfjG HCXQa ef GdfHjP s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(2/392) s
Keywords: (3GdCOHs